2020
DOI: 10.3389/fcimb.2020.544335
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Prevalence and Subtype Diversity of the Intestinal Protist Blastocystis sp. in a Gut-Healthy Human Population in the Czech Republic

Abstract: Blastocystis sp. is a common intestinal protist colonizing the human intestine the prevalence of which varies across non-industrialized and industrialized countries. Its role in the human gut ecosystem remains unclear due to persisting gaps in knowledge of epidemiology and factors affecting gut colonization. Here, we aimed to expand the knowledge of the epidemiology of Blastocystis sp. in the gut-healthy humans in one of the industrialized European countries, including the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 84 publications
5
52
0
1
Order By: Relevance
“…Blastocystis is a common inhabitant of the large intestine of many animals and over a billion people worldwide ( Stensvold and Clark, 2016 ). In developing countries, Blastocystis prevalence in human population can reach 84% ( Poulsen et al, 2016 ) and 100% ( El Safadi et al, 2014 ), and prevalence in industrialized countries ranges between 7 and 50% ( Bart et al, 2013 ; Scanlan et al, 2014 , 2016 ; Seyer et al, 2017 ; Lhotská et al, 2020 ). Yet the role Blastocystis plays in human health and disease is still unclear and the subject of ongoing debate ( Lukeš et al, 2015 ; Chabé et al, 2017 ; Stensvold et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Blastocystis is a common inhabitant of the large intestine of many animals and over a billion people worldwide ( Stensvold and Clark, 2016 ). In developing countries, Blastocystis prevalence in human population can reach 84% ( Poulsen et al, 2016 ) and 100% ( El Safadi et al, 2014 ), and prevalence in industrialized countries ranges between 7 and 50% ( Bart et al, 2013 ; Scanlan et al, 2014 , 2016 ; Seyer et al, 2017 ; Lhotská et al, 2020 ). Yet the role Blastocystis plays in human health and disease is still unclear and the subject of ongoing debate ( Lukeš et al, 2015 ; Chabé et al, 2017 ; Stensvold et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Within the genus Blastocystis , 28 genetic groups named as subtypes (STs) have been proposed, based on polymorphism in the SSU rRNA gene [ 14 , 15 ]. Of the 28 proposed subtypes, 22 subtypes (ST1–ST17, ST21, ST23–ST26) have been acknowledged as legitimate subtypes meeting the criteria of having SSU rDNA sequences that differ by 4% or more [ 14 , 16 ]. These subtypes have been named using a numbering system that is currently sequential and based on publication date.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies should be however pinpointed that performed Blastocystis detection and typing in the presently reported populations. Petrášová et al reported data from six researchers working at a Tanzanian primate forest reserve (all 6 were positive) [ 28 ]; Lhotská et al studied volunteers in Czechia, finding a 24.3% (12/49) positivity in children [ 29 ], not significantly different from the present report; Alfellani et al studied a rather heterogeneous collection of datasets that also included Nigerian patients (adults, with 49% positivity) [ 9 ]. Finally, rural children in Nigeria were studied by Poulsen et al [ 30 ] who reported a prevalence of 84% in the village of Illero in Western Nigeria.…”
Section: Discussionmentioning
confidence: 68%